Internet e investigación cualitativa - Aurora Tovar Ramírez (Revista Mexicana de Ciencias Políticas y Sociales)
Chris Mann y Fiona Stewart, Internet Communication and Qualitative Research. A Handbook for Researching Online, Sage Publications Ltd., Londres, 2000, 258 pp.